Cytotoxicity of adducts formed between quercetin and methylglyoxal in PC-12 cells. (1st August 2021) - Liu, Pengzhan; Yin, Zhao; Chen, Min; Huang, Caihuan; Wu, Zhihui; Huang, Junqing; Ou, Shiyi; Zheng, Jie
Highlights: Two quercetin-methylglyoxal (MGO) adducts were detected in cookies. These adducts exhibited higher neurotoxicity than MGO in PC-12 cells. They interfere Akt-Nrf2-HO-1/NQO-1 pathways. They induce mitochondria dysfunction. Abstract: Quercetin (Que) or quercetin-containing food stuffs are widely incorporated in bakery foods for improving food texture and health effects, and scavenging reactive aldehydes, such as methylglyoxal (MGO) that exhibits various deleterious effects including contribution to neurodegeneration. This study aimed to investigate the cytotoxicity of the adducts formed between quercetin and MGO resulted from the incorporation of quercetin in foods. Two highly-purified adducts (Que-mono-MGO and Que-di-MGO) were found to display higher cytotoxicity than their precursor MGO and quercetin. They elevated apoptosis via upregulation of expression of apoptotic markers, including p-P38, cleaved caspase-9 and -3, and pro-apoptotic Bax. They induced mitochondrial dysfunction via decreasing mitochondrial membrane potential and increasing lactate dehydrogenase release. Moreover, they attenuated levels of p-Akt, Nrf2, NQO-1, and HO-1, proving that they induced neurodegeneration apoptosis through mitochondria-mediated signaling pathways (PI3K-Akt and Nrf2-HO-1/NQO-1). These findings indicated that the safety consequence of MGO after scavenged by polyphenols needs to be concerned.